(untitled) - Gurewich, Nathan (Indianapolis, 1995)
Explains Visual Basic programming techniques step by step; Uses shaded syntax boxes, techniques, as well as Q&A, Do/Don't, and workshop sections to highlight key points and reinforce learning
Keywords: Visual Basic,Visual basic,BASIC (Computer program language),BASIC (Ngôn ngữ lập trình máy tính)